Kapazitiv gekoppelte Streifenleitungsantennen für Millimeterwellenanwendungen - Mayer, Jonathan (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2022)
Radar is an important part of autonomous driving and allows an appropriate environment recognition. The contribution of this work is a new arrangement of capacitively coupled patches and a holistic view on substrates under different environmental conditions. Thus, an optimized design can meet reliability and bandwidth requirements.